Pre-combustion carbon dioxide capture materials - Wang, Qiang (Royal Society of Chemistry, 2018)
An introduction to the different inorganic adsorbents/sorbents used in pre-combustion carbon dioxide capture.
Keywords: Carbon dioxide mitigation.; elektronické knihy; electronic books